Implementation of Sociology Learning Model Problem Based Learning Based on Quizizz in Class XI IIS 1 SMAS Mujahidin Pontianak - Manisah, Ayu; Ulfah, Maria; Okianna, Okianna (Universitas Tanjungpura, 2024)
Penelitian ini berjudul